2004
DOI: 10.1093/jn/134.11.3100
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Menaquinone Is Associated with a Reduced Risk of Coronary Heart Disease: The Rotterdam Study

Abstract: Vitamin K-dependent proteins, including matrix Gla-protein, have been shown to inhibit vascular calcification. Activation of these proteins via carboxylation depends on the availability of vitamin K. We examined whether dietary intake of phylloquinone (vitamin K-1) and menaquinone (vitamin K-2) were related to aortic calcification and coronary heart disease (CHD) in the population-based Rotterdam Study. The analysis included 4807 subjects with dietary data and no history of myocardial infarction at baseline (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
401
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 471 publications
(431 citation statements)
references
References 30 publications
12
401
3
8
Order By: Relevance
“…Vitamin K 2 even reduced the risk of severe arterial calcification by 52% (OR: 0.48). 43 Carboxylated MGP is an important inhibitor of vascular calcification. Accordingly, uncarboxylated MGP (ucMGP) is an independent risk factor for arteriosclerosis.…”
Section: Vascular Healthmentioning
confidence: 99%
“…Vitamin K 2 even reduced the risk of severe arterial calcification by 52% (OR: 0.48). 43 Carboxylated MGP is an important inhibitor of vascular calcification. Accordingly, uncarboxylated MGP (ucMGP) is an independent risk factor for arteriosclerosis.…”
Section: Vascular Healthmentioning
confidence: 99%
“…Conversely, the administration of vitamin K1 allows for normal coagulation production, yet does not prevent peripheral vascular calcification (29). In the Rotterdam study, a large epidemiologic trial investigating the relationship of nutritional intake to cardiovascular disease, vitamin K2 intake was inversely related to both vascular calcification and mortality (30), whereas vitamin K1 intake seemed to have no relationship, a finding noted by others (31). These studies suggest that vitamin K2-dependent peripheral carboxylation protects the vasculature from calcification and raises important questions about the bioavailablity of vitamin K2.…”
Section: The ␥-Carboxylation Process: Converting Vkdps Into Their Actmentioning
confidence: 99%
“…The population based Rotterdam study studied 4807 healthy men and women older than age 55 years, evaluating the relationship between dietary intake of vitamin K and aortic calcification, heart disease, and all-cause mortality. The study revealed that high dietary intake of vitamin K2-at least 32 mcg per day, with no intake of vitamin K1, was associated with a 50% reduction in death from cardiovascular issues related to arterial calcification and a 25% reduction in all-cause mortality [14].…”
Section: Vitamin K2 the "New Kid On The Block"mentioning
confidence: 97%